2022
DOI: 10.3389/fpsyg.2022.984661
|View full text |Cite
|
Sign up to set email alerts
|

Naive independent directors, corporate governance and firm performance

Abstract: This paper mainly explores the effect of naive independent directors on firm performance. Using hand-collected data on Chinese listed companies, this study finds that the proportion of naive independent directors is positively associated with firm performance, and an increased proportion of naive independent directors reduce the probability of tunneling of controlling shareholders and financial distress. The findings are robust after using alternative explanatory variables and retro-causality tests. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…For example, increased trustworthiness may reduce creditors' perceived risk, improve financing conditions, and lower the company's loan cost (Bacha et al, 2021). In a similar vein, Chen et al (2022) found that independent directors are less likely to have conflicts of interest with management, which may improve their supervisory effectiveness. Furthermore, the ability of individuals to question managerial choices and promote openness can improve corporate governance, reducing loan risk, and debt expenses (Chaudhary, 2022;Chen et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 92%
“…For example, increased trustworthiness may reduce creditors' perceived risk, improve financing conditions, and lower the company's loan cost (Bacha et al, 2021). In a similar vein, Chen et al (2022) found that independent directors are less likely to have conflicts of interest with management, which may improve their supervisory effectiveness. Furthermore, the ability of individuals to question managerial choices and promote openness can improve corporate governance, reducing loan risk, and debt expenses (Chaudhary, 2022;Chen et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 92%
“…The agent theory holds that there is information asymmetry between the agent and the principal, and the agent may use this information asymmetry to damage the interests of the principal. Furthermore, principals and agents have different goals, leading to conflicts of interest in their relationship [43]. Management plays an important role in resolving the principal-agent conflict problem [44].…”
Section: Heterogeneity Analysis Based On Corporate Governance Qualitymentioning
confidence: 99%